2017
DOI: 10.1089/gtmb.2016.0384
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Circulating miR-17-92 Cluster and HDAC9 Gene in Atherosclerotic Patients with Unstable and Stable Carotid Plaques

Abstract: Levels of the miR-17-92 cluster in plasma and HDAC9 gene expression in peripheral blood cannot be considered appropriate biomarkers to identify patients with unstable plaques at risk of rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Conversely, the miR 30-CSE-H 2 S axis prevents myocardial cell ischemic injury (MI) by regulating the production of hydrogen sulfide (H 2 S). miR-30 family repression after MI provides potential therapeutic value for the normal functioning of the heart [74, 75]. The endoplasmic reticulum (ER) is a membranous and multifunctional organelle that is involved in many processes in the majority of animal cells, cardiomyocytes and vascular cells included.…”
Section: Effect Of the Mir-17-92 Cluster On Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the miR 30-CSE-H 2 S axis prevents myocardial cell ischemic injury (MI) by regulating the production of hydrogen sulfide (H 2 S). miR-30 family repression after MI provides potential therapeutic value for the normal functioning of the heart [74, 75]. The endoplasmic reticulum (ER) is a membranous and multifunctional organelle that is involved in many processes in the majority of animal cells, cardiomyocytes and vascular cells included.…”
Section: Effect Of the Mir-17-92 Cluster On Disease Statesmentioning
confidence: 99%
“…Researchers have speculated that the downregulation of the miR-30 family induces ER stress and related upregulation of GRP78 in the cardiovascular system, as the involvement of miR-30 produces a positive effect toward ER stress. miR-30 has proved to be a viable method of alleviating diseases connected with ER stress [75]. Notably, the miR-17-92 cluster is considered to be differentially expressed in cardiomyocytes at various developmental stages, but, among the many cardiac miRNAs, little is known about whether miR-17-92 provides regulatory mechanisms in heart disease (Figure 1).…”
Section: Effect Of the Mir-17-92 Cluster On Disease Statesmentioning
confidence: 99%
“…Studies have shown that the HDAC9 SNP allele of rs3757720 is associated with coronary heart disease, which is a marker of atherosclerosis 2) . In the mice knockout HDAC9 gene, the extent of atherosclerosis lesions was decreased significantly 4) . This indicates that the absence of HDAC9 expression can result in the downregulation of inflammation-related genes and upregulation of lipid-related genes 5,13) .…”
Section: Discussionmentioning
confidence: 99%